(untitled) (Mustansiria Dental Journal, 2018)
Aims This retrospective cephalometric study was designed to evaluate and correlate the hyoid bone position and angulations in two groups of subjects exhibiting vertical and horizontal mandibular rotation. Material & method: Each group consisted of 50 subjects (25 males and 25 females) with skeletal class I pattern. Cephalometric data were obtained and four measurements were used to locate the hyoid bone in 3 aspects 1. Vertical, 2. Horizontal and 3. Angular. Thirteen angular and linear measurements were used to evaluate mandibular rotation and facial morphology. Result: There were statistically significant differences in vertical position, horizontal distances and angulations of hyoid bone measurements between the vertical and horizontal group subject (P<0.05). These measurements were significantly correlated with mandibular rotation angles. Conclusion: In vertical mandibular rotation group subjects, the hyoid bone showed to be more inferior and posterior position with downward inclination. While in horizontal mandibular rotation group subjects, the hyoid bone was more superior and anterior position with relatively upward angulations.